A Review on Phytochemical Pharmacological and Biological Activities of Thuja Occidentalis - Bharti, Keshav; Sharma, Manmohan; Vyas, Girish Kumar; Sharma, Dr. Shailesh (Asian Journal of Pharmaceutical Research and Development, 2022)
Thuja occidentalis plant of Cupressaceae family originated in Eastern North America and is now planted as an ornamental tree in Europe and Brazil, where it is known as the "tree of life" or "white cedar." It's often used to treat liver problems, enuresis, amenorrhea, bullous bronchitis, psoriasis, cystitis, uterine carcinomas, diarrhoea, and rheumatism in traditional medicine. Due to the presence of essential oil, coumarins, flavonoids, tannins, and proanthocyanins, the chemical ingredients of T. occidentalis have piqued researchers' curiosity for decades. Antioxidant, anti-inflammatory, antibacterial, antifungal, anticancer, antiviral, gastrointestinal tract protective action, radioprotection, antipyretic, and lipid metabolism regulating activity are all examples of pharmacology. As a result, the current study is a compilation of all essential material for T. occidentalis, including phytochemical, biological and a detailed examination of their pharmacological properties.The current review represents a synthesis of all relevant information for Thuja occidentalis, including phytochemical, biologicaland a thorough analysis of their pharmacological activities, in order to promote all of the biological activities demonstrated thus far, rather than focusing on a single biological activity.